Housing Quantum and Innovative Building Systems in South Africa – the Affordability Perspective for 2020 - Emmanuel Kabundu; Sijekula Mbanga; Brink Botha; Gerrit Crafford (Critical Housing Analysis)
The adoption of innovative building technologies (IBTs) and social welfare policies in South Africa has facilitated an increase in decent homeownership among low-income groups, thus improving their quality of life. However, due to the escalating costs of building materials, the capital and lifecycle costs of implementing these technologies may no longer be affordable. This research aims to provide a comparative evaluation of the affordability of some readily available IBTs in the South African construction industry, relative to existing homeownership subsidy grants. The method used involved the use of secondary data for these IBTs and the income constraint methods. The results showed that, apart from the technologies suitable for the provision of temporary structures, most of the other technologies were not affordable for the complete subsidisation of the top structure when both capital and lifecycle costs were used, except the Moladi and Robust structure IBTs under some low-income homeownership programmes. Further analysis using credit-linked subsidies revealed that the minimum household income required to achieve affordable homeownership (and their rankings) depends both on the evaluation technique (lifecycle or capital costs) and technology used. To improve affordability, any implementing government can either raise the amount of the top structure subsidy grant, promote the use of cheaper but durable IBTs, or promote the use in incremental building methods, such as the Enhanced People’s Housing Process (EPHP) for the case of South Africa.